“The Battle of Grand Pré”: The Historic Sites and Monuments Board of Canada and the Commemoration of Acadian History - Marsters, Roger (Acadiensis, 2006)
Abstract In the 1920s and 1930s members of the Historic Sites and Monuments Board of Canada (HSMBC) debated how best to represent the past’s ethnic and linguistic diversity. Some board members espoused a “bicultural” view of Canadian history that aimed to subsume francophone and anglophone experience in a unified civic history, posited as a corrective to the linguistic strife then vexing Canada. The HSMBC’s commemorative projects at Grand Pré, Nova Scotia, forced members to confront entrenched ethnic and linguistic rivalries — conflict that challenged and finally undermined their commitment to this incipient biculturalism.